Video game‐based exercise in children and adolescents with non‐cystic fibrosis bronchiectasis: A randomized comparative study of aerobic and breathing exercises. Issue 9 (21st June 2022) - Ucgun, Hikmet; Gurses, Hulya Nilgun; Kaya, Meltem; Cakır, Erkan
Abstract: Background: Video game‐based systems have been proposed to improve effectiveness and compliance with exercise training in children and adolescents with noncystic fibrosis bronchiectasis (NCFB). This study aimed to investigate the effects of aerobic and breathing video game‐based exercises (VGE) on pulmonary function, respiratory and peripheral muscle strength, functional capacity, and balance in children and adolescents with NCFB. Method: Thirty‐nine children and adolescents aged between 8 and 18 years with NCFB were randomly allocated into three groups as "home‐based chest physiotherapy group" (CP), "aerobic VGE given in addition to home‐based chest physiotherapy group" (CP + aerobic VGE), and "breathing VGE given in addition to home‐based chest physiotherapy group" (CP + breathing VGE). All three groups performed chest physiotherapy program twice a day for 7 days per week for 8 weeks. Pulmonary function, respiratory and peripheral muscle strength, functional capacity, and balance were assessed at baseline and after 8 weeks of training. Results: The improvement in maximum expiratory pressure and balance scores were significantly higher in both CP + aerobic and CP + breathing VGE groups. The significant improvement in maximum inspiratory pressure was greater in the CP + breathing VGE group. The changes in peripheral muscle strength and functional capacity were significantly higher in the CP + aerobic VGE group. Conclusions: The present study showed that aerobic VGE provides additional benefits in improving peripheral muscle strength and functional capacity, while breathing VGE provides further increase in improving respiratory muscle strength. In addition, both aerobic and breathing VGE were effective in improving balance, but they were not superior to each other.